User's perceptions on thermal comfort and the effects of radiation in Skycourts of high rise buildings. - Abdullah, Aldrin (Universiti Sains Malaysia, 2014)
There is a great need to reduce energy consumption in high-rise office buildings due to the escalating environmental problems such as Urban Heat Island effect. Sky courts provides a natural way of cooling, allowing natural ventilation and inviting natural lighting without relying on the use of air-conditioning to achieve thermal comfort. Introducing greenery in high-rise buildings help to improve the thermal comfort where the microclimate is highly influenced by solar radiation.